ATRT-16. CONGENITAL RHABDOID TUMORS AS A MAJOR CLINICAL CHALLENGE - A COLLABORATIVE EUROPEAN EFFORT. Issue 2 (22nd June 2018) - Nemes, Karolina; Clément, Nathalie; Kachanov, Denis; Bens, Susanne; Shamanskaya, Tatyana; Varfolomeeva, Svetlana; Kerl, Kornelius; Abbink, Floor; Ebinger, Martin; Tippelt, Stephan; Graf, Norbert; Hasselblatt, Martin; et al.
Abstract: In general patients with congenital rhabdoid tumors (RT) are considered to be incurable and often treated using a primarily palliative approach. METHODS: A pro- and retrospective collection of 42 patients from EU-RHAB, France and Moscow (2006 to 2016) diagnosed within the first 28 days of life was evaluated. Genetic and clinical evaluation included SMARCB1 and/or SMARCA4 (FISH, MLPA, sequencing) mutation analysis and immunohistochemistry. 48% (20/42) were treated according to the EU-RHAB recommendations, 7% (3/42) following the pilot approach Rhabdoid 2007, 33% (14/42) with individual schedules and 12% (5/42) received no chemotherapy. RESULTS: 40.5% (17/42) of patients presented with extracranial RT, 33.5% (14/42) with AT/RT and the remainder 26% (11/42) demonstrated synchronous tumors. Metastases at diagnosis were present in 52% (22/42). A germ-line mutation (GLM) was detected in 66% (25/38) and associated with a poor prognosis (4.2 ± 4.1% vs. 48 ± 16.4%, p<0.00005). A total resection (GTR) was realized in 17%. GTR (42.9 ± 18.7% vs. 4.9 ± 4.3%, p=0.04), therapy according to a standardized approach (20.9 ± 8.7 % vs. 7.1 ± 6.9 %, p=0.0018) and CR (23.6 ± 9.8% vs. 1.3 ± 3.6%, p=0.04) were significant prognostic factors. CONCLUSIONS: In many instances cure is not possible in congenital RT and a palliative approach warranted. However, a positive impact of standardized therapeutic approaches on survival was noted making a tailored approach toward affected patients and their families mandatory. Supported by grants to MCF by the "Deutsche Kinderkrebsstiftung" DKKS 2010.03 and the parents organization Lichtblicke, Augsburg.